1998
DOI: 10.1046/j.1365-2648.1998.00708.x
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of the effectiveness of focus groups as a method of qualitative data collection with Chinese populations in nursing research

Abstract: Although there has been a significant increase in the use of focus groups as a qualitative method of data collection in health and nursing research, literature on the use of this method with Chinese populations is limited. This study was therefore undertaken to explore the contribution of focus groups as a method of data collection amongst Hong Kong Chinese women. The study involved the comparison of the data obtained from two concurrent research studies which both employed case study design and focus groups a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
124
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(127 citation statements)
references
References 20 publications
2
124
0
Order By: Relevance
“…Consistent with the findings of Twinn's [15] study, the current study lends further support to the use of focus groups as a good tool for gathering evaluation data with the Chinese populations. Two salient conclusions can be drawn from this study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Consistent with the findings of Twinn's [15] study, the current study lends further support to the use of focus groups as a good tool for gathering evaluation data with the Chinese populations. Two salient conclusions can be drawn from this study.…”
Section: Discussionsupporting
confidence: 87%
“…Nabors and colleagues [18,19] utilized focus groups for an assessment of program needs, strengths, weaknesses, and to gain ideas for future program development. Recognizing the importance of exploring the contribution of focus groups as a method of qualitative data collection with Chinese populations, Twinn [10,15] conducted several studies in nursing research and concluded in her study [15] that focus groups can be used with Chinese populations. She provided quotations from the data to support her conclusion that the research study with focus groups design yielded rich and in-depth data, participants were willing to participate, and that the method is appropriate, with the proviso that groups and analysis are conducted in the participants' first language.…”
Section: Introductionmentioning
confidence: 99%
“…Group dynamics such as 'dominance' may occur (Henderson 1995, Twinn 1998 and hostility or suspicion between members can hamper discussion (Bloor et al 2001). There may be a tendency towards 'polarisation' where participants express more extreme views than in private or may impart more information than intended (Morgan and Kruger 1993).…”
Section: Methodsmentioning
confidence: 99%
“…The provision of services such as epidural pain relief, ability to perform caesarean section, and availability of medical personnel was similar in all units apart from high dependency neonatal care, which was only available in the city hospitals. Authors have worked with groups of five or six participants and as few as three (Twinn 1998, Lane et al 2001, Kitzinger and Barbour 1999. A pilot study was conducted to assess recruitment strategies, sample size, and collect preliminary data (Polit and Beck 2004).…”
Section: Recruitmentmentioning
confidence: 99%
“…The goal is to discover new ideas and insights that can help people to explore and clarify their views (Morgan, 1998). The number of participants (three to four per group discussion) was suitable because of the need for a translator and cross-cultural research (Twinn, 1998). Following up the focus-group interviews with individual interviews allows deeper insight into certain aspects of the chosen topics (Krueger, 1998b;Strickland, 1999;Roer-Strier et al, 2005).…”
Section: Data Collectionmentioning
confidence: 99%